2016
DOI: 10.4084/mjhid.2016.047
|View full text |Cite
|
Sign up to set email alerts
|

“Identifying High-Risk Chronic Lymphocytic Leukemia: A Pathogenesis-Oriented Appraisal of Prognostic and Predictive Factors in Patients Treated With Chemotherapy With or Without Immunotherapy.”

Abstract: Chronic lymphocytic leukemia (CLL) displays an extremely variable clinical behaviour. Accurate prognostication and prediction of response to treatment are important in an era of effective first-line regimens and novel molecules for high risk patients. Because a plethora of prognostic biomarkers were identified, but few of them were validated by multivariable analysis in comprehensive prospective studies, we applied in this survey stringent criteria to select papers from the literature in order to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 103 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…Defining the TL in CLL might help predict the disease risk and propose a specific therapeutic course for patients, as shorter telomeres have a strong association with an inferior progression free survival (PFS) and disease aggressiveness (29,30,34,40,42,46,47,57,58).…”
Section: Telomere Length Studiesmentioning
confidence: 99%
“…Defining the TL in CLL might help predict the disease risk and propose a specific therapeutic course for patients, as shorter telomeres have a strong association with an inferior progression free survival (PFS) and disease aggressiveness (29,30,34,40,42,46,47,57,58).…”
Section: Telomere Length Studiesmentioning
confidence: 99%
“…The prognosis is better in patients with mutated IgVH genes than in those without the mutation. 12,13 A high expression of CD38 and ZAP-70 constitute a negative prognostic factor. 14,15 Disorders of apoptosis are also postulated to play an important role in CLL, and the induction of programmed cell death by some medications is a determinant of successful therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that up to 90% of CLL with CK show an U-IGHV mutational status [ 22 23 , 28 29 ] a relationship may exist between the IGHV gene configuration and the development of CK. Indeed a large body of evidence showed that the lymphocytes with U-IGHV i) respond to antigen stimulation by activating intracellular signalling, ii) undergo cell divisions in vivo as shown by incorporation of deuterated water, iii) carry relatively shorter telomeres and, iv) tend accumulate genomic defects [ 40 41 ]. Interestingly, Burns and co-workers [ 42 ], used a whole exome sequencing approach to study gene mutations in correlation with the IGHV gene configuration and found that exonic CLL driver gene lesions were more common in U-IGHV CLL than in CLL with mutated IGHV gene.…”
Section: Resultsmentioning
confidence: 99%
“…Herling and colleagues did not find a significant association between CK and the U- IGHV status in the patients enrolled in the CLL11 trial [ 24 ], possibly due to over-representation of IGHV -unmutated cases and consequent low number of IGHV -mutated cases in this analysis including patients with disease progression. These findings are not surprising, since TP53 and ATM function are involved in maintaining genomic stability [ 66 67 ], and the U- IGHV configuration identifies a CLL clone that is responsive to B-cell receptor antigen stimulation with consequent cell activation [ 40 41 ].…”
Section: Resultsmentioning
confidence: 99%